ANALISIS GALIAN DALAM PADA BASEMENT GEDUNG DENGAN PERMODELAN SOFT SOIL MENGGUNAKAN PROGRAM PLAXIS - Fahriani, Ferra (SIPIL, 2013)
Excavation causes soil deformation and changes in stress and strain. This research takes on a case study in the basement construction project of a skyscraper in Jakarta. The construction method used is top down method. The Diafragma, with a thickness of 0,6 meter and length of 37 meter, was constructed to the excavation. A professional software based on the concept of Finite Element Method, âPLAXIS 2Dâ, was chosen for the analysis. The soil example used in this research is Cam Clay (Soft Soil) using drained and undrained analysis and effective parameter. The result shows that drained analysis gives bigger values of deformation and bending moment than undrained analysis, so the safety factor is smaller. Undrained analysis gives a prediction result that is more similar with the result of deformation measurement in the field. For the surface movement, the result is bigger when using drained analysis than when using undrained analysis. The big surface movement occurs in 5-10 m length. However, the behavior of stress and strain in the Soft Soil modeling is similar to the condition in the field. Key Words: excavation, drained analysis, undrained analysis, cam clay